Perancangan Arsitektur Untuk Pendukung Pengambilan Keputusan Pemilihan Program Studi Perguruan Tinggi Menggunakan Differential Aptitude Test (DAT) - Erwan Yani; Dede Kurniadi (AMIK Garut, 2015)
Learning in Higher Education is a dream of almost every student graduates high school/vocational and equivalent. Selection of the right program study will determine the success of students in taking classes and the impact on the student career in the future. Thus the decision of the selection of appropriate courses needed by students and parents to be able to determine a good future. The unfortunate from a great desire to go to college, is less matures they choose a major or program of study in college. As a result, many new students who failed in the middle of the street or drop out when they have been accepted at colleges and many students who have entered acceptable then move the program of study because it does not conform with the ability even to decide to quit college because of discrepancies selected majors. The purpose of this study is to support the candidate that is not wrong in determining the majors in college. The result of the design of the system architecture of decision making in the selection of the courses are web-based system SPK Program who applied online are connected to the Internet which can be accessed at any time without limited by space and time, so as to help students choose courses that interest. The results of this study is the design and implementation planning application systems such as DSS System for selection study program. Keywords: architecture system, decision support system, differential aptitude test, enterprise system